Black Intellectuals and the Dilemmas of Race and Class in Trinidad - Turner, Mary (Labour / Le Travail, 1985)
This article reviews the book, "Black Intellectuals and the Dilemmas of Race and Class in Trinidad," by Ivaar Oxaal.
Keywords: DOCHERTY, Charles; Nonfiction; REVIEWS; STEEL & Steelworkers: The Sons of Vulcan (Book); Steel industry; books